THE RELATIONSHIP BETWEEN STUDENTS’ HABITS OF WATCHING MOVIE AND THEIR ENGLISH LISTENING ABILITY - Huda, Innayatul; Talib, Ahmad; Tahir, Muh. (Universitas Negeri Makassar, 2023)
The objective of this study is to find the relationship between students’ habits of watching English movies and their English listening ability. This research is a correlational study using quantitative methods in collecting data from students’ habits of watching English movie and their listening ability. The sample of this study was the students in grade XI (Al-Farisi, Al-Battani, Al-Ghazali) SMA Negeri 13 Pangkep. The instruments used in this study were a questionnaire and a listening ability test. The sample of the research was chosen using simple random sampling, the research took thirty students. Then, tests students’ listening ability by listening to audio and completing the gaps in a dialogue/conversation. The scores from both instruments were calculated and analyzed by using a statistical procedure of Product Moment Correlation to see if there was any relationship between the two variables. The findings showed that there is no relationship, with the index value of the correlation coefficient (rxy) of -0.244. Furthermore, the hypothesis testing showed that (rxy) was much lower than the correlation coefficient of the Product Moment Table (rt). which means that the null hypothesis (Ho) was accepted. In conclusion, there is no significant relationship between students’ habits of watching English movie and their listening ability.